Selfish Attack detection mechanism using COOPON in Cognitive Radio (International Journal of Engineering and Computer Science, 2016)
Cognitive radio is one of the wireless based communication technology. This technology is mainly designed to allow the unlicensed users to utilize the maximum bandwidth available in the network. An important consideration to any wireless network is secure communication. In Cognitive radio (CR), the unlicensed users use the maximum available bandwidth. When the spectrum is not used by the licensed primary user, the free channels are allocated for the unlicensed secondary users (SUs). But the problem is that some of the secondary users act selfishly to occupy all the channels. These secondary users are called as selfish attackers.  Hence, to detect a selfish attacker COOPON (Cooperative neighboring cognitive radio Nodes) detection technique is used. The proposed work provides COOPON system which detects multiple selfish attacks and evaluate  the detection rate by considering the parameters like selfish secondary user density, number of secondary nodes and number of neighboring nodes using  MATLAB R2012a (version7.14.0.739).